Construction of Critical Reasoning Skills Assessment Instruments as Diagnostic Assessments in Physics Learning with Polytomus Scoring - Ekawati, Elvin Yusliana; Sabrilla Almas Azzahra; Hanun Fithriyah (Journal of Education Reseach and Evaluation, 2024)
The availability of tests specifically designed to measure initial critical reasoning skills in Physics still needs to be improved in terms of availability and innovation. This shows a need for more innovative and effective instruments to measure students' critical reasoning skills in Physics. This research aims to produce a vital reasoning ability assessment instrument with polytomous scoring in Phase E Physics learning in Alternative Energy material as a diagnostic assessment. This type of research is mixed research. The data collection method used was a questionnaire using an instrument as a questionnaire sheet. The data sources were nine experts and 62 students from 3 schools. The results showed that the 12 items of the diagnostic assessment instrument of students' initial critical reasoning ability with the Quest program were in a suitable category. The conclusion of this study provides information on the construction of critical reasoning ability assessment instruments worth using to diagnose students' critical reasoning abilities. This diagnostic assessment instrument can be implemented in physics learning, especially during assessment activities, to measure students' essential reasoning skills at the beginning of learning so that teachers can decide on learning designs by student profiles. This study has several implications, one of which is that using assessment instruments with a polynomial assessment allows for a more in-depth and detailed evaluation of student understanding.